Evaluation Study of Kota Lama Semarang Revitalization - Muhammad Azmy Ikhsani; Safety Husna Pangestika; Artanti Kusuma Ayu (Jurnal Koridor, 2025)
Kota Lama Semarang area is one of the icons of Semarang City and a tourist destination with its own charm in which there are various old buildings from the Colonial era. The Kota Lama Semarang area has been revitalized since 2017 which aims to maintain and preserve existing buildings and improve the quality of the area. The Kota Lama Semarang area has now become a leading tourist destination in Semarang City after revitalization, but after revitalization there are still some problems left behind where it becomes a record of the success of revitalization. The purpose of this research is to evaluate the implementation of revitalization in the Kota Lama Semarang to show that the implementation of revitalization has not been fully successful. This research uses qualitative approach with descriptive method. In general, the revitalization carried out in the Kota Lama Semarang Area has been successfully carried out and has a good impact from the social and tourism aspects which are reviewed from 4 points namely Urban Live Quality, Sustainable Urban Form and Structure, Capital / Asset Improvement, and Social and Economic. However, from the review there are still shortcomings, namely from the cultural and economic aspects where the revitalization carried out has less impact, especially for the community around the Kota Lama Semarang.